The effect of early detection of breast cancer education on the knowledge and practice of doing awareness in female students - Mei Anna Ekha Wahyuning; Yuni Purwati (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Breast cancer is one of the highest causes of death in women in Indonesia with a prevalence of 41.8% in 2022. However, most women in Indonesia still minimally do their own breast examination (BSE), so their knowledge and practice are still low. Early detection through breast self-examination (BSE) is important to reduce the incidence of breast cancer. Health education is needed to increase the knowledge and practice of BSE in adolescent girls. Purpose: To determine the effect of early detection of breast cancer education on the knowledge and practice of conducting BSE on female students. Method: Quasi-experimental research with pretest and posttest non-equivalent control group designs on 50 respondents selected by purposive sampling. The research instruments are in the form of a knowledge questionnaire and a checklist of breast examination practices. Data analysis used the Wilcoxon and Mann Whitney tests. Results: Posttest showed that most of the knowledge of the intervention group was in the category of sufficient (96%) and less than 1 (4%), and the control group was in the category of sufficient 19 (76%) and less than 6 (24%). While the intervention practice was in the category of good 25 (100%) and the control group was less than 24 (96%), sufficient 1 (4%). The results of the Mann Whitney Test showed a p value of 0.476 (>0.05) in knowledge and 0.000 (<0.05) in practice. Conclusion: Early detection of breast cancer education has no effect on the knowledge and practice of conducting BSE in female students.